2006
DOI: 10.1007/s10840-006-9009-5
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency catheter ablation of atrioventricular nodal reentrant tachycardia in a patient with orthotopic heart transplantation by bicaval anastomosis

Abstract: Patients with orthotopic heart transplantation may have a variety of arrhythmias. There are reports of successful radiofrequency catheter ablation of some of them. Two months after orthotopic cardiac transplantation by bicaval anastomosis, a 49-year-old man developed episodes of tachycardia. The patient developed with dyspnoea and hypotension during typical atrioventricular nodal reentrant tachycardia (AVNRT) revealed by electrocardiogram. During programmed atrial stimulation with progressively increasing prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Furthermore, although more than one-half of the reported cases required ablation within 1 month, RFA was curative in all cases. Cases of AVNRT reported in post-OHT patients are rare (1,2,5). Once again, RFA with slow pathway modification was effective at treating AVNRT in all cases.…”
Section: Avrt and Avnrt After Transplantationmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, although more than one-half of the reported cases required ablation within 1 month, RFA was curative in all cases. Cases of AVNRT reported in post-OHT patients are rare (1,2,5). Once again, RFA with slow pathway modification was effective at treating AVNRT in all cases.…”
Section: Avrt and Avnrt After Transplantationmentioning
confidence: 77%
“…Transplanted hearts provide a unique model to study the management of these arrhythmias, because of the relative autonomic denervation and the pro-arrhythmic characteristics of surgical scars. Previous studies have reported atrioventricular nodal (AVNRT) and atrioventricular reentrant tachycardias (AVRT) in transplanted patients due to pre-existing accessory pathways and dual atrioventricular nodal physiology in the donor hearts (1)(2)(3)(4)(5). Macroreentrant atrial tachycardias (ATs) from pro-arrhythmic substrates originating at surgical anastomotic sites have also been reported (6 -9).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the true etiologies of many of these tachyarrhythmias are not identified, and the reported incidences of symptomatic AVNRT in OHT patients are limited. In spite of anatomic and autonomic differences compared with non‐OHT patients, RF catheter ablation has been reported to yield successful elimination of AVNRT in OHT patients . Our patient has been free of any cardiac symptoms since the ablation, and a second biopsy continues to be negative for rejection.…”
Section: Discussionmentioning
confidence: 69%
“…In our case, the donor heart developed AVNRT after 3 months without any evidence of rejection on the endomyocardial biopsy. Few case reports have documented this phenomenon . Transplanted hearts undergo major surgical distortion of cardiac anatomy subsequently leading to surgical scars, which are known to be arrhythmogenic .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation